Detection and characterization of Leptospira spp. in dogs diagnosed with kidney and/or liver disease in Selangor, Malaysia - Abdul Rahman, Mohammad Sabri; Khor, Kuan Hua; Bejo, Siti Khairani; Lau, Seng Fong; Mazlan, Mazlina; Roslan, Azri; Goh, Soon Heng (SAGE Publications, 2021)
Leptospirosis is a serious bacterial disease that affects both humans and animals. A wide range of symptoms have been described in humans; the disease in dogs is commonly associated with kidney and/or liver disease. In Malaysia, information about the common serovars infecting dogs is limited. Therefore, we investigated the occurrences of leptospirosis in 124 pet dogs diagnosed with kidney and/or liver disease. Blood, urine, abdominal effusion, and/or kidney and liver were collected from the dogs. Based on microscopic agglutination testing, 53 of 124 (42.7%) dogs were seropositive for leptospiral exposure. Sera were frequently positive to serovars Bataviae (n = 12), Javanica (n = 10), and Icterohaemorrhagiae (n = 10). Direct detection using PCR showed that 42 of 124 (33.9%) of the whole blood and 36 of 113 (31.9%) urine samples were positive for pathogenic Leptospira spp. By PCR, 2 of 23 (9.1%) kidney and 2 of 23 (9.1%) liver were positive for pathogenic Leptospira spp. Abdominal effusion from 4 dogs were PCR-positive for pathogenic Leptospira spp. The species detected were L. interrogans, L. borgpetersenii, L. kirschneri, and L. kmetyi by partial 16S rRNA sequencing. We further identified and characterized 11 Leptospira spp. isolates from 8 dogs as serovars Bataviae, Javanica, and Australis. The mortality rate of the Leptospira-infected dogs was high (18 of 53; 34%).